Well‐defined multispecies probiotic and enzyme combination outperforms traditional fermented probiotic applications in an intensive Pacific white shrimp, Litopenaeus vannamei (Boone, 1931), culture system. Issue 1 (24th November 2022) - Novriadi, Romi; Prihadi, Tri Heru; Saragih, Hartati Sri Devi; Kesselring, Jutta; Standen, Benedict
Abstract: A series of treatments were designed to evaluate the efficacy of feeding commercial multispecies probiotics feeding with enzymes and fermentation process on the growth parameters and culture environment of Pacific white shrimp, Litopenaeus vannamei (Boone, 1931), in an intensive culture system. Commercial multispecies probiotics and enzymes (PEs) were continuously applied in three different doses, namely (i) 0.2, (ii) 0.4, and (iii) 0.6 mg L −1 and designated as 0.2, 0.4, and 0.6 PE during the first 30 days of intensive culture of Pacific white shrimp, L . vannamei (Boone, 1931). The probiotics were continually applied every alternate day, while the enzymes were added every sixth day throughout the trial period. The PE dose for all treated tanks was increased by 0.2 ppm after 30 days of culture and another 0.2 ppm after day 60. Meanwhile, fermentation technique, which has become the common method applied in Indonesia in the control treatment, was added on the same day with the PE group with increasing dosage, following the same trend with the 0.6 PE group. Results showed that the group receiving 0.6 PE showed higher final biomass, higher mean weight, and protein retention efficiency as well as a lower feed conversion ratio compared with the control treatment. Abundance of Vibrio spp. remained below 10 3 cfu mL −1 throughout the trial. Water quality indicators TAN, NO2 N and NO3 N peaked in weeks 3–5 and then declined after that until the end of the culture period in all tanks. This decline was significantly faster in PE‐treated tanks. Multispecies PEs have potential applications in controlling Vibrio spp., maintaining proper water quality condition, and enhancing the growth of shrimp in intensive culture system.